Use of VKAs and NOACs as stroke prophylaxis in patients with atrial fibrillation - a review of the literature - Jama, Grzegorz; Kmiotek, Weronika; Różańska-Smuszkiewicz, Gabriela; Smuszkiewicz-Różański, Paweł; Oronowicz, Radosław; Wesołek-Bielaska, Ewelina; Kuzio, Agnieszka; Cieplińska, Aleksandra; Ziojła-Lisowska, Kinga; Piasecka, Zuzanna (Quality in Sport, 2024)
Introduction and Purpose: Stroke is a common complication of one of the most common cardiac arrhythmias, atrial fibrillation. The aim of this study is to provide key information about these diseases and to compare the drugs used to prevent stroke. Materials and methods: A literature search was conducted using the medical databases PubMed and Google Scholar. Articles were retrieved in English, employing the key words: “VKA “, „NOAC”, „atrial fibrillation”, „anticoagulants“ and „stroke” appropriate configurations. Conclusions: According to the recommendations and available medical literature, the use of NOACs is usually the most appropriate choice for stroke prevention in patients with atrial fibrillation. However there are also clinical situations, in which the use of VKAs would be more appropriate.